Expanding access to administrative data: the case of tax authorities in Finland and the UK - Verho J.; Almunia M.; Harju J.; Kotakorpi K.; Tukiainen J. (Springer New York LLC, 2022)
We discuss typical issues in getting access to and using high-quality administrative tax data for research purposes. We discuss research involving both quasi- and field experiments implemented together with the tax authority. We reflect on practical solutions that promote co-creation of knowledge and reduce information asymmetries between researchers and practitioners, based on our experiences of working with the tax authorities in Finland and the UK. We provide examples of how to improve the overall research environment focusing on two successful case studies: the HMRC Datalab in the UK and the remote access to data from Statistics Finland. We propose two key arguments to persuade policymakers elsewhere to follow similar practices: improved data security and equality of access across researchers.